Exploring the Impact of Flexible Working Hours on Job Satisfaction: The Mediating Role of Work-Life Balance - Raisa Jabbar; Ali Sajjad; Qalander Buksh Ali (UW Journal of Management Sciences, 2025)
Purpose: This study’s purpose was to find out the relationship between flexible working hours and job satisfaction, about how work-life balance acts as a mediator in the education sector. Thus, the study attempted to see how flexible working hours affect employees’ job satisfaction and whether work-life balance mediates such a relationship. Design and Methodology: According to online surveys, Google Forms was used to sample 112 education sector personnel to get quantitative research designs. Sampling methods were used to generate data analyzed using Structural Equation Modeling (SEM) under Smart PLS. The study developed the link between flexible working hours, work-life balance, and job satisfaction. Findings: Flexible working hours greatly increase worker job satisfaction, according to the study. Flexible schedules also improve work-life balance, which has a beneficial impact on job satisfaction. The results indicate that the favorable effect of flexible scheduling on total job satisfaction is amplified by work-life balance, which partially mediates the association between flexible hours and job satisfaction. Implications: According to the report, introducing flexible working hours in the educational sector will greatly improve employee happiness. Another partial mediator that raises satisfaction levels is a greater focus on work-life balance. Thus, there is a strong argument for managers in the education sector to implement flexible work practices to boost employee performance and retention rates, in addition to job satisfaction.